Optimal target blood pressure for major adverse cardiovascular and cerebrovascular events in hypertensive patients: a nationwide population-based study. Issue 1 (January 2022) - Kim, Seon-Mi; Kim, Do-Hyang; Ryu, Dong-Ryeol; Lee, Soojin; Kim, Yaerim; Park, Sehoon; Cho, Semin; huh, Hyuk; Hwang, Jinseub; Lee, Jung-Pyo; Han, Seung-Seok; Lee, Hajeong; et al.
Abstract : N/A: Background: Generalizing an 'optimal' blood pressure (BP) level for individuals with hypertension remains controversial due to the implementation of different medical guidelines. This study investigated the association of BP with major adverse cardiovascular and cerebrovascular events (MACCE) and determined the optimal BP for patients with hypertension. Method: A total of 934 179 individuals who received antihypertensive medications were selected from the National Health Insurance Service Examination Database between 2003 and 2011 in Korea. Their BP was measured at the index date, which was the first health examination. The study outcomes were MACCE, including acute myocardial infarction, heart failure, stroke, and all-cause mortality. The participants were monitored until in December, 2017. The hazard ratios were calculated using Cox proportional hazard models. The cumulative incidence of MACCE for each BP group was estimated using the Kaplan–Meier method. Results: A lower risk of MACCE was observed at a SBP of 120–129 mmHg and a DBP of 80–89 mmHg. The endpoint-specific incidence rates and hazard ratios for acute myocardial infarction, heart failure, stroke, and all-cause mortality were the lowest at a SBP of 120–129 mmHg and a DBP of 80–89 mmHg. Conclusion: Even though this observational study did not support inference of a causal relationship, a SBP of 120–129 mmHg and a DBP of 80–89 mmHg may be safely recommended considering the possibility of MACCE in Korean patients with hypertension. In addition, the target BP should be tailored individually according to age, sex, and comorbidities. Abstract : Supplemental Digital Content is available in the text